An introduction to probability with Mathematica - Kao, Edward P. C. (World Scientific, 2022)
"The main objective of this text is to facilitate a student's smooth learning transition from a course on probability to its applications in various areas. To achieve this goal, students are encouraged to experiment numerically with problems requiring computer solutions"--Provided by publisher.